ANALISIS PEMBIAYAAN REFINANCING DAN RISIKO PADA AKAD MUSYARAKAH MUTANAQISHAH PRODUK KEPEMILIKAN RUMAH (KPR) DI PERBANKAN SYARIAH KOTA BANDUNG - Melitha Dwi Putri1,A. Jajang W. Mahri, 2 Suci Aprilliani Utami3 (UIN Mataram, 2019)
There are various kinds of akads used in the financing of House ownership (PKR) Sharia banking, one of which is Misharaka Mutanaqisah contract (MMq). But the financing through the Musharaka Mutanaqisah (MMq) is a few obstacles generally in the banking world, among them are insufficient internal processes, system failure, and human error. This research aims to see how the implementation in the Mutanaqisah contract (MMq) refinancing financing is in accordance with Fatwa DSN MUI number: 89/DSN-MUI/XII/2013 about refinancing (Sharia refinancing) and researching risks That can happen to the product of mortgage Musharaka Mutanaqisah (MMq). This research uses quantitative descriptive methods. The population is the customer of KPR refinancing Musharaka Mutanaqisah (MMq) which amounted to 33 people with census techniques. Instruments on this study use questionnaires. As for risk analysis use interview techniques to practitioners, academics, and regulators. The results showed implementation of Musharaka Mutanaqisah (MMq) Financing of refinancing on KPR products in good category, although there are several indicators in the category quite.